2022
DOI: 10.3390/su14020702
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Novelties within the Circular Economy Concept under the Digital Transformation of Society

Abstract: The study makes, under a new configuration of the circular economy, a cross-country analysis based on the Competitiveness and Innovation Indicators in the E.U., i.e., two sub-criteria: private investments, jobs, and gross value added; and patents related to recycling and secondary raw materials as a proxy for innovation. The analysis proved that investments influence the number of patents, and participate in societal transformation. A further cluster analysis classified countries on the level of innovation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…A study conducted by Riesener et al (2019) discussed about nine success factors in two phases of production system for the implementation of CE with the help of digital transformation technologies. Implementation of innovative procedures, solution and blockchain technology can greatly impact the role of CE in reducing environmental problems (Ili c et al, 2022). A recent study done by Maiurova et al (2022) showed the solid waste management in Russia using CE paradigm.…”
Section: Circular Economy and Covid-19 Pandemicmentioning
confidence: 99%
“…A study conducted by Riesener et al (2019) discussed about nine success factors in two phases of production system for the implementation of CE with the help of digital transformation technologies. Implementation of innovative procedures, solution and blockchain technology can greatly impact the role of CE in reducing environmental problems (Ili c et al, 2022). A recent study done by Maiurova et al (2022) showed the solid waste management in Russia using CE paradigm.…”
Section: Circular Economy and Covid-19 Pandemicmentioning
confidence: 99%
“…The strategy of CEI is alleged to be an important act of economic growth, to strengthen the quality of life among societies, drive systematic change, sustain values and the circulation of material, and eliminate waste among societies [33]. Due to these reasons, many practitioners observe CEI as the best model for economic development among societies.…”
Section: Relationship Between Cei and Dsmentioning
confidence: 99%
“…A circular economy may be able to address systemic issues and provide adequate conditions for developing a secure data management solution utilizing blockchain technology [1][2][3]. While taking into account the country's risk premium assessment elements, coherent data management will result in economic risk reduction, a decline in unemployment, thriving foreign investments, and GDP (gross domestic product) growth [2,3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A circular economy may be able to address systemic issues and provide adequate conditions for developing a secure data management solution utilizing blockchain technology [1][2][3]. While taking into account the country's risk premium assessment elements, coherent data management will result in economic risk reduction, a decline in unemployment, thriving foreign investments, and GDP (gross domestic product) growth [2,3]. There is no doubt that anyone involved in socioeconomic or societal activities will eventually realize how important a circular economy is concerning the preservation of data warehouses, economic expansion, and the creation of new jobs as the main sources of innovation and competitive advantages, the efficient use of resources by businesses [4][5][6][7].…”
Section: Literature Reviewmentioning
confidence: 99%